IS THERE A RELATION BETWEEN PARASITISM AND TAIL AUTOTOMY IN LIZARDS? CASE STUDY IN LIOLAEMUS DARWINII (IGUANIA: LIOLAEMIDAE) - Castillo, Gabriel N. (2022)
Tail autotomy acts as anti-predatory mechanism in a great diversity of lizard species. Research links tail loss with various aspects of lizard life history. However, parasitic aspects are not taken into consideration, despite being a variable that greatly influences reptile ecology. For the first time, it is proposed that the existence of a relationship between the caudal autotomy of a lizard species is related to its parasitic condition. We studied 30 adult specimens of Liolaemus darwinii Bell, 1843 in the desert of Monte, San Juan province, Argentina. Autotomy was used as a direct measure of predator-prey interaction. A series of variables were analyzed that could be related to tail autotomy. The following variables were studied using generalized linear models: sex, environments (disturbed vs. conserved), condition (parasitized vs. not parasitized), parasitic intensity, weights (g) and snout-vent length (Lhc). The dependent variable (presence of tail: 1, absence of tail: 0) was adjusted to a binomial distribution, whose link function is logit (logistic regression). Only the variable parasitized vs. non-parasitized condition was significantly associated with tail autotomy. Parasitized individuals all have cut tails or in some stage of regeneration. Individuals that were not parasitized had complete tails (intact). The results establish for the first time a relationship between parasitism and tail loss in L. darwinii. The results are discussed in a behavioral ecological context and physiological resource allocation. In addition, our work is an approach to understanding the role of parasites in the ecology of L. darwinii in the Monte desert in Argentina.